Emerging Infectious Uveitis - Chee, Soon-Phaik; Khairallah, Moncef (Springer International Publishing : Imprint: Springer, 2017)
This book reviews the various emerging infectious diseases that show a significant association with uveitis, describing and explaining their ocular manifestations with the aid of color illustrations. In addition, it presents brief reports of further emerging infections that are associated with uveitis in rare cases. The coverage is wide ranging, encompassing diverse emerging bacterial, viral, parasitic, and fungal infections. Individual chapters are also devoted to important re-emergent diseases such as syphilis and tuberculosis, with the focus on new data on epidemiology, diagnosis, and management. Emerging infectious diseases are defined as "those whose incidence in humans has increased within the past two decades or threatens to increase in the near future". Emergence may be due to the spread of a new agent, to the recognition of an infection that has been present in the population but has gone undetected, or to the realization that an established disease has an infectious origin. This book will be an invaluable source of information on all aspects of uveitis in these diseases.- Resumé vydavatel
Keywords: infekční nemoci; uveitida; oftalmologie; infectious diseases; uveitis; ophthalmology; elektronické knihy; kolektivní monografie; electronic books; collective monographs